Urban sustainability in Latin America. Challenges and perspectives - González Couret, Dania (Revista Científica de Arquitectura y Urbanismo, 2016)
ABSTRACT: The article examines the evolution of ideas and some good practices concerning urban sustainability as a basis to explore possible futures for city planning in Latin America, based on the current situation on the continent. The paper is structured in three steps, starting with the theoretical framework of concepts and principles as well as their evolution. Based on that, the current situation in Latin American cities is characterized, in order to undertake the third step o proposing possible solutions, taking into account problems and potentialities, as well as good practices in this and other continents. Results and discussions are focused on ways to be followed in order to contribute to the development of more sustainable cities in the region. Sustentabilidad urbana en América Latina. Retos y perspectivas RESUMEN. En el artículo de examina la evolución de las ideas y algunas buenas prácticas en relación con la sustentabilidad urbana como base para explorar posibles futuros para el planeamiento de ciudades en América Latina, a partir de la situación actual en el continente. El trabajo se estructura en tres etapas, comenzando con el marco teórico de conceptos y principios, así como su evolución. Sobre esa base, se caracteriza la presente situación en las ciudades de América Latina, teniendo en cuenta problemas y potencialidades, así como buenas prácticas en este y otros continentes. Los resultados y discusión se concentran en las vías a seguir para contribuir al desarrollo de ciudades más sustentables en la región. PALABRAS CLAVE: desarrollo sustentable, América Latina, urbanismo